How long can the term of office of the Polish parliament last? A legal-constitutional analysis - Litwin, Tomasz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
The main research aim of this article is an analysis of the length of the parliamentary term of office in Poland based on the analysis of legal rules. According to the art. 98 para. 1 of the Constitution, the parliamentary term of office starts on the day on which the Sejm assembles for its first sitting and ends on the day preceding the first assembly of the newly elected Sejm. Although the mentioned rule also expressly states that parliamentary term of office lasts 4 years, the length of the particular terms of office could be very different. If the parliamentary term of office is shortened, it could last even less than two months. If it is prolongated because of the introduction of the extraordinary measure, it could last approx. 5 years (in case of emergency state), or it maximal length can not be defined. Moreover, even in case of the “normal” terms of office they could have different length - slightly less than 4 years or longer than 4 years by even a few weeks. The presented considerations lead to the conclusion that there is need to make certain amendments of the rules of law concerning this area, which would ensure minimal 4 years length of the “normal” parliamentary term and regulate the organisation of the parliamentary elections after the termination of the extraordinary measure. Author analysed the legal rules basing on legal-dogmatic method and interpreted them by using such methods of their interpretation as: language-logical, teleological and systematic.

Głównym celem naukowym artykułu jest analiza zagadnienia długości kadencji polskiego parlamentu w oparciu o analizę przepisów prawnych. Zgodnie z art. 98 ust. 1 Konstytucji kadencja parlamentu rozpoczyna się w dniu pierwszego posiedzenia Sejmu, a kończy w dniu poprzedzającym pierwsze posiedzenie nowo wybranego Sejmu. Pomimo, że przepis ten również wyraźnie stwierdza, że kadencja parlamentu trwa 4 lata, długości poszczególnych kadencji mogą być bardzo różne. W przypadku skrócenia kadencji parlamentu może ona trwać nawet mniej niż 2 miesiące. Natomiast w przypadku jej przedłużenia w wyniku wprowadzenia stanu nadzwyczajnego może ona trwać nawet około 5 lat (stan wyjątkowy) lub też jej maksymalna długość nie jest określona. Co więcej, nawet w przypadku „normalnych” kadencji mogą one mieć różne długości - trwać krócej niż 4 lata lub dłużej niż 4 lata, nawet o kilka tygodni. Przedstawione rozważania prowadzą do wniosku, że w omawianym zakresie należałoby dokonać pewnych zmian w przepisach prawnych, które gwarantowałyby co najmniej 4-let- nią długość „normalnej” kadencji parlamentu oraz regulowałyby organizację wyborów po zakończeniu stanu nadzwyczajnego. Autor analizując przepisy prawne bazował na metodzie prawno-dogmatycznej, a dokonując interpretacji przepisów prawnych korzystał z następujących metod wykładni: językowo- logicznej, celowościowej i systemowej.
Jak długa jest kadencja polskiego parlamentu? - analiza prawno-ustrojowa
Keywords: Sejm; Senate; parliament; term of office; The Constitution of the Republic of Poland from 1997; Sejm; Senat; parlament; kadencja; Konstytucja RP z 1997 r.